PENGARUH KERAGAMAN MEDIA DAN IMBALAN EKSTERNAL TERHADAP NIAT BERBAGI PENGETAHUAN MAHASISWA DAN DOSEN AKUNTANSI - Kartika Kartika (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2010)
The aim of this research is to examine the factors supporting individuals’ knowledge sharing intention. Based on the theory of reasoned action, this study examined influenced of extrinsic reward, and channel richness to knowledge sharing intention. Data was collected using a field study of lecturer and student in university at Malang. We employ independent sample t-test and PLS (Partial Least Squares) version 2.0. The result show that there isn’t perception difference betwen student and lecturer about factors that supporting knowledge sharing intention. The result show that channel richness has played significant part influenced attitude toward knowledge sharing. Extrinsic reward imposed no impact on an individual’s attitude toward knowledge sharing. The result from this study confirm the theory of reasoned action. This study also find that subjective norm greater influence knowledge sharing intention than attitude toward knowledge sharing. Keywords: theory of reasoned action, extrinsic rewards, channel richness